A new natural hybrid of Sphagneticola (Asteraceae, Heliantheae) from Guangdong, China - Huimin, Li; Ren, Chen; Yang, Qin-Er; Yuan, Qiong (Phytotaxa, 2015)
A new natural hybrid, Sphagneticola × guangdongensis (Asteraceae, Heliantheae), is described and illustrated. Its chromosome number was revealed to be 2n = 53, lending strong support for its hybridity and parental origin (S. calendulacea with 2n = 50 and S. trilobata with 2n = 56) as previously already confirmed by evidence from morphology and molecular data.